Micro plasma source design using WGMs a PANDA ring - Siriroj, R.; Srinuanjan, K.; Yupapin, P. P. (My University, 2014)
Plasma is a one of state of matter that is produced by applying energy into gas or fluid like, where the ionized electrons from gas or fluid atoms to be free electrons. In this paper, the use of micro plasma source generation by using a PANDA ring resonator is introduced, in which the whispering gallery modes (WGMs) are formed within the center ring and can be used to create the high power of electromagnetic wave for gas plasma production. In application, the micro plasma source can be fabricated in small scale material process or others suitable operation. In this case, the plasma source can be decreased to be micro-scale device, where in fact, the common plasma source system size is large because the high energy source to produce high power plasma is required. Finally, the detail of using such small scale plasma source is discussed. The theoretical details of whispering gallery mode and quantum tunneling effects are also reviewed and discussed. © (2014) Trans Tech Publications, Switzerland.
Keywords: Micro-optics; Microring resonator; Panda ring; Plasma source; Vehicle power source